2018
DOI: 10.3934/microbiol.2018.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of immune-related genes during Nora virus infection of <em>Drosophila melanogaster</em> using next generation sequencing

Abstract: Drosophila melanogaster depends upon the innate immune system to regulate and combat viral infection. This is a complex, yet widely conserved process that involves a number of immune pathways and gene interactions. In addition, expression of genes involved in immunity are differentially regulated as the organism ages. This is particularly true for viruses that demonstrate chronic infection, as is seen with Nora virus. Nora virus is a persistent non-pathogenic virus that replicates in a horizontal manner in D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 50 publications
(64 reference statements)
2
30
0
Order By: Relevance
“…In our case, we failed to detect any considerable up-regulation of immune genes in the cellular response to either TV or DMelNV. Interestingly, the time course analysis of the response to DMelNV found that expression of immune related genes increased overtime (Lopez et al, 2018). As the time of infection is an important factor to regulation of the host transcriptome, and the scRNAseq data used here is from 5-7 days old flies, we may have failed to detect a more substantial change to the host transcriptome.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…In our case, we failed to detect any considerable up-regulation of immune genes in the cellular response to either TV or DMelNV. Interestingly, the time course analysis of the response to DMelNV found that expression of immune related genes increased overtime (Lopez et al, 2018). As the time of infection is an important factor to regulation of the host transcriptome, and the scRNAseq data used here is from 5-7 days old flies, we may have failed to detect a more substantial change to the host transcriptome.…”
Section: Discussionmentioning
confidence: 83%
“…The fact that disruption of essential genes in the interactome might diminish the infection process of pathogens, in accordance with the centrality-lethality rule (Jeong et al, 2001;Ahmed et al, 2018), corroborates with the first hypothesis; whereas the fact that some cells exhibited a large amount of DMelNV RNA and the expression of some ribosomal protein genes is negatively correlated to DMelNV replication level corroborates with the latter hypothesis. Interestingly, previous microarray and bulk RNA-seq studies were unable to find a similar under-expression of ribosomal genes in DMelNV-infected flies (Cordes et al, 2013;Lopez et al, 2018). In fact, some ribosomal proteins were over-expressed in the bulk RNA-seq data (supplementary file S1).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations